2010
DOI: 10.1177/1531003510386495
|View full text |Cite
|
Sign up to set email alerts
|

Technique of Reversed Flared Iliac Stent Graft for Iliac Aneurysms With Discrepant Size Diameters

Abstract: The technique of reversed flared iliac stent graft limb is a feasible option in patients with iliac aneurysms and significant discrepancy in the diameter of the iliac arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…If a bell-bottom 19 or flared stent-graft limb technique was employed, patients received either a flared limb from the manufacturer of the main body stent-graft, an aortic extension cuff, or an aortouni-iliac conversion device using methods previously described. 17,19,20 All overlapping graft segments were molded with a compliant balloon, and completion digital subtraction angiography was obtained to Postoperative CT surveillance with arterial and delayedphase venous imaging was typically obtained at 1, 6, and 12 months and annually thereafter unless radiographic findings dictated otherwise. Timing and need for any reintervention was based on the attending surgeon's judgment.…”
Section: Evar Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…If a bell-bottom 19 or flared stent-graft limb technique was employed, patients received either a flared limb from the manufacturer of the main body stent-graft, an aortic extension cuff, or an aortouni-iliac conversion device using methods previously described. 17,19,20 All overlapping graft segments were molded with a compliant balloon, and completion digital subtraction angiography was obtained to Postoperative CT surveillance with arterial and delayedphase venous imaging was typically obtained at 1, 6, and 12 months and annually thereafter unless radiographic findings dictated otherwise. Timing and need for any reintervention was based on the attending surgeon's judgment.…”
Section: Evar Proceduresmentioning
confidence: 99%
“…Furthermore, off-label techniques for landing in large iliac arteries are often reported, such as inverted aortouni-iliac devices and "bell-bottom" techniques using aortic cuffs. [15][16][17] Limited and conflicting results exist with regard to the natural history and outcomes of using aneurysmal CIA (aCIA) LZs during EVAR. Some series have demonstrated good short and midterm outcomes, while larger registry data suggest that the presence of an iliac aneurysm can lead to a higher risk of type Ib leak, limb occlusion, secondary intervention, or aneurysm rupture after EVAR.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] An FE can enhance filament adherence in regions where the luminal diameter changes markedly. 20 Park et al 22 reported that compared to SE stents, FE stents exhibited less stent displacement (2.4% vs. 15.4%) and reduced the complication risk in those with diseases of the digestive system. Previous studies on patients with intracranial vascular diseases found that FDs may become displaced or shortened to various extents.…”
Section: Discussionmentioning
confidence: 99%
“…To re-load it, squeezing it with surgical umbilical strips or multiple silk ties or inserting it into the peel-away sheath may be helpful ( Fig. 1 – 3 ) [ 8 , 9 ]. However, manual reinsertion is different from that of the original production process.…”
Section: Discussionmentioning
confidence: 99%